Maillard Reaction Products in Gluten-Free Bread Made from Raw and Roasted Buckwheat Flour - Maria Barbara Różańska; Aleksander Siger; Artur Szwengiel; Krzysztof Dziedzic; Sylwia Mildner-Szkudlarz (Molecules, 2021)
The formation of Maillard reaction products (MRPs) in gluten-free bread made from roasted and raw buckwheat flour was examined. The levels of phenolic compounds such as flavonoids (catechin, naringenin, quercetin, rutin, and others) and phenolic acids (like 4-hydroxybenzoic, caffeic, dihydroxybenzoic, ferulic, gallic, syringic, vanillic, and p-coumaric) were measured using reversed-phase ultra-high performance liquid chromatography-electrospray ionization mass spectrometry (RP–UHPLC–ESI-MS). Early and advanced Maillard reaction products were analyzed using HPLC, whereas spectrofluorimetric analysis was used to determine the levels of fluorescent intermediate compounds (FIC). The total levels of phenolic compounds were higher in the case of buckwheat bread prepared from roasted buckwheat flour (156 and 140 µg/g of crumb and crust, respectively). Rutin, gallic acid, and catechin were the most abundant phenolic compounds detected in roasted buckwheat bread. The roasting process resulted in significantly lower radical scavenging capacities (ABTS) of the total phenolics and flavonoids in the buckwheat bread. Taking into consideration these Maillard reaction products, we observed a significant increase in FIC level in roasted buckwheat crumb and crust (at about 40%, and 38%, respectively). At the same time, the Nε-(carboxymethyl)lysine (CML) level did not change in roasted or raw buckwheat bread crumb, though in roasted buckwheat crust the concentration of CML increased by about 21%.